Effects on skin dose from unwanted air gaps under bolus in an MR-guided linear accelerator (MR-linac) system. (12th March 2021) - Huang, Chen-Yu; Yang, Bin; Lam, Wai Wang; Tang, Ka Keung; Li, Ting Chuan; Law, Wai Kong; Cheung, Kin Yin; Yu, Siu Ki
Abstract: Bolus is commonly used in MV photon radiotherapy to increase superficial dose and improve dose uniformity for treating shallow lesions. However, irregular patient body contours can cause unwanted air gaps between a bolus and patient skin. The resulting dosimetric errors could be exacerbated in MR-Linac treatments, as secondary electrons generated by photons are affected by the magnetic field. This study aimed to quantify the dosimetric effect of unwanted gaps between bolus and skin surface in an MR-Linac. A parallel-plate ionization chamber and EBT3 films were utilized to evaluate the surface dose under bolus with various gantry angles, field sizes, and different air gaps. The results of surface dose measurements were then compared to Monaco 5.40 Treatment Planning System (TPS) calculations. The suitability of using a parallel-plate chamber in MR-Linac measurement was validated by benchmarking the percentage depth dose and output factors with the microDiamond detector and air-filled ionization chamber measurements in water. A non-symmetric response of the parallel-plate chamber to oblique beams in the magnetic field was characterized. Unwanted air gaps significantly reduced the skin dose. For a frontal beam, skin dose was halved when there was a 5 mm gap, a much larger difference than in a conventional linac. Skin dose manifested a non-symmetric pattern in terms of gantry angle and gap size. The TPS overestimated skin dose in general, but shared the same trend with measurement when there was no air gap, or the gap size was larger than 5 mm. However, the calculated and measured results had a large discrepancy when the bolus-skin gap was below 5 mm. When treating superficial lesions, unwanted air gaps under the bolus will compromise the dosimetric goals. Our results highlight the importance of avoiding air gaps between bolus and skin when treating superficial lesions using an MR-Linac system.